The influence of gut-decontamination prophylactic antibiotics on acute graft-versus-host disease and survival following allogeneic hematopoietic stem cell transplantation. (2nd January 2017) - Routy, Bertrand; Letendre, Caroline; Enot, David; Chénard-Poirier, Maxime; Mehraj, Vikram; Séguin, Noémie Charbonneau; Guenda, Khaled; Gagnon, Kathia; Woerther, Paul-Louis; Ghez, David; Lachance, Silvy
ABSTRACT: The intestinal microbiota plays a key role in the pathogenesis of acute graft-versus-host disease (aGVHD). High-dose conditioning regimens given prior to allogeneic hematopoietic stem cell transplantation (aHSCT) modulate the composition of gut microbiota and damage the gut epithelial barrier, resulting in increased systemic inflammation. We assessed whether gut decontamination with antibiotics (ATB) prior to aHSCT influenced the frequency of aGVHD and mortality in 500 patients from two Canadian centers between 2005 and 2012. The rate of grade II–IV aGVHD was higher in the ATB arm compared with the arm without ATB (42% vs 28%; p < 0.001). This difference was mainly driven by a 2-fold higher rate of grade II–IV gastrointestinal aGVHD (GI-GVHD) in the ATB arm compared with the arm without ATB (20.7% vs 10.8%; p = 0.003). Multivariate analyses adjusted for known aGVHD risk factors revealed that more patients in the ATB group developed clinically significant GI-GVHD and liver aGVHD; adjusted odds ratio (aOR) = 1.83; p = 0.023 and aOR = 3.56; p = 0.047, respectively. Importantly, median overall survival (OS) was significantly lower in the group receiving ATB and the OS at 10 y remained decreased in the ATB group; adjusted hazard ratio (aHR) = 1.61 ( p < 0.001). Without undermining the role of ATB prophylaxis to prevent infection in aHSCT, we have shown that the use of ATB that targets intestinal bacteria is associated with a more severe aGVHD that involves the GI organs and impacts OS. Prospective studies that evaluate the contribution of bacterial decontamination to aGVHD are warranted.